Optimizing the Parameters of Spark Plasma Sintering to Enhance the Hardness of MgO/TiC Composites - Sai Ashish Kumar Karanam; R. Rathinam; Pradeep Kumar Mouria; Arnold C. Alguno; Rey Y. Capangpangan; Tariku Achamyeleh; Jose Luis Arias Gonzales; Vijay Kumar Sharma; T. Stephen Livingston (Advances in Materials Science and Engineering)
In this research, the first work was carried out to manufacture MgO-based metal matrix composite containing 3 wt%. Sintering parameters, such as temperature, pressure, and time were subjected to Taguchi analysis to identify the most significant effect on magnesium oxide physical and mechanical characteristics. The impact of each sintering parameter explores using the analysis of variance-structure and microstructure analysis using XRD and EDS-equipped FE-SEM. The mechanical properties of the composite are evaluated by testing its Rockwell hardness (HR) and Vickers hardness (HV). The results showed that sintering temperature was the most influential of the sintering factors on microhardness. Densification at its peak was 100%, while it peaked at 62.19 Rockwell hardness and 58.7 Vickers hardness.